Optimization of Pichia pastoris Expression System for High-Level Production of Margatoxin - Naseem, Muhammad Umair; Tajti, Gabor; Gaspar, Attila; Szanto, Tibor G.; Borrego, Jesús; Panyi, Gyorgy (Frontiers in Pharmacology, 2021)
Margatoxin (MgTx), is a high affinity blocker of voltage gated potassium (Kv) channels. It inhibits Kv1.1-Kv1.3 ion channels in picomolar concentration. This toxin is widely used to study physiological function of Kv ion channels in various cell types, revealing possibilities to cure channelopathies. Isolation of native MgTx in large quantity from scorpion venom is not affordable. Whereas chemical synthesis and recombinant production in E. coli need in vitro oxidative refolding for proper disulfide bond formation, resulting in a very low yield of peptide. Pichia pastoris expression system offers an economical and better approach to overcome all these limitations and gives higher yield of correctly refolded recombinant peptides. Here, we improved in heterologous expression of recombinant MgTx (rMgTx) in P. pastoris by using preferential codons, selecting the hyper-resistant clone against Zeocin, and optimizing the culturing conditions. We produced 36±4 mg/L of >98% pure His-tagged rMgTx (TrMgTx) which is 3-folds higher yield than the previous reports. Proteolytic digestion of peptide with factor Xa generated untagged rMgTx (UrMgTx). In pharmacological study using electrophysiology both tagged and untagged rMgTx blocked the Kv1.2 and K1.3 currents with comparable potency to the native MgTx (kd for Kv1.2 were 65 and 15 pM, and for Kv1.3, 85 and 50 pM, respectively). The binding kinetics showed that TrMgTx has lower association rate than UrMgTx for both Kv1.2 and Kv1.3. The dissociation rate of both analogues was same for Kv1.3. However, in case of Kv1.2 TrMgTx showed surprisingly much higher dissociation rate with full recovery of the block in contrast to UrMgTx. Moreover, in biological functional assay, both peptides significantly downregulated the expression of early activation markers IL2R and CD40L in activated CD4+ TEM lymphocytes through Kv1.3 blockade. In conclusion, we report that Pichia expression system is a powerful method to produce disulfide rich peptides and overexpression could be enhanced noticeably through optimization strategies, making it more cost-effective. Since the presence of the His-tag on MgTx mildly altered the block equilibrium and binding kinetics, recombinant toxins could be used in ion channel research without removing the tag and thus, it further reduces the cost of toxin production.